Meaning making in service of power at the climate change negotiations : a critical discourse analysis of the speeches held by Xi Jinping and Barack Obama at the opening ceremony of COP21 - Söderlund, Christoffer (SLU/Dept. of Urban and Rural Development, 2016)
Human induced climate change is already beginning to affect the world, and the increasing amount of research relating to climate change is showing that the effects will intensify over the coming century if nothing is done to change society. Still very little substantial change is to be seen. In this paper I investigate part of the problem with changing course by utilising the concept of ideology and employing it in a Critical Discourse Analysis of speeches held by two of the world’s most powerful individuals, President Barack Obama and President Xi Jinping, at the opening ceremony of COP21 in Paris. The analysis is focused on how climate change is portrayed, what the goals of the agreement should be and what the solutions to climate change are, according to the speeches. This is combined with a focus on what ideological discourses are used, and how climate change is incorporated in these ideological discourses. The analysis shows that, although the speeches have their separate characteristics, they draw on and reinforce largely the same discourses; neoliberalism and nationalism. Both speeches portray climate change as a phenomenon with long lasting consequences for human society and the main threats are perceived to be decreasing economic growth and potential instability of the nation-state. Climate change is also incorporated in the neoliberal ideology through an inspiration discourse, portraying climate change as an opportunity to extend the market and privatise commons. At the same time nature is reduced to resources for the economy and human society is reduced to its economy and nation-state.